Real-world Bleeding Outcomes and Costs Following Vascular Graft Anastomosis Using PROLENE Sutures with HEMO-SEAL Technology in Patients Undergoing Abdominal Aortic Aneurysm Repair - Nadia Y. Sutton; Niels-Derrek Schmitz (Journal of Health Economics and Outcomes Research)
# Background Suture hole bleeding is a common complication of vascular graft anastomosis that has potential to prolong vascular procedures, increase costs, and compromise patient outcomes.